The wavelet transform function to analyze interplanetary scintillation observations. Issue 10 (20th May 2014) - Aguilar‐Rodriguez, E.; Rodriguez‐Martinez, M.; Romero‐Hernandez, E.; Mejia‐Ambriz, J. C.; Gonzalez‐Esparza, J. A.; Tokumaru, M.
Abstract Interplanetary scintillation (IPS) observations are useful to remotely sense the inner heliosphere. We present a new technique to analyze IPS observations using a wavelet transform (WT) function. This technique allows us to derive, in a straightforward way, a simple method to obtain the scintillation index (m). We tested this WT technique to analyze IPS observations obtained by the Solar‐Terrestrial Environment Laboratory (STEL) radio telescope. The analysis of the m index of the radio source 3C48 detected by STEL over the year 2012 shows the expected decrease with solar elongation reported in previous studies. The WT technique has a great potential for future solar wind studies using IPS observations from contemporary radio telescopes.